PATRIARCHAL CULTURE AND ITS EFFECT TO THE CHARACTER IN THE YELLOW WALLPAPER - Alia Nisa Alexandrina Raushanfikr; Ilda Cholifatul Ummah; Shabrina An Adzhani (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
This study describes the impact of patriarchal culture on the main character in the short story The Yellow Wallpaper. The concept of patriarchy reflects a social system in which dominance and privilege are primarily held by men, thus bringing significant implications to women's lives. Through narrative analysis, this research reveals the dominance of the main character, John, as the main control in the narrator's life and the excessive focus on domestic life that inhibits women's freedom. This research uses descriptive qualitative methodology with Spradley's data analysis technique, grounded in Walby's patriarchy theory, to identify patriarchal elements in the story and analyze their impact. The results show that patriarchal culture creates limitations on women's freedom and autonomy, detailing the suppression of individual freedom, reliance on male authority, distrust of women's experiences, and restrictions of gender stereotypes. Overall, this short story provides a clear picture of the negative impact patriarchal structures have had on women's lives over the years. Keyword: patriarchy, patriarchal impact, short story, The Yellow Wallpaper